Innovating neurosurgical training: a comprehensive evaluation of a 3D-printed intraventricular neuroendoscopy simulator and systematic review of the literature - Saemann, Attill; De Rosa, Adriana; Zubizarreta Oteiza, Jokin; Sharma, Neha; Thieringer, Florian M.; Soleman, Jehuda; Guzman, Raphael (Frontiers in Surgery, 2024)
ObjectiveThe objective of this study was to develop and evaluate a low-cost 3D-printed simulator to improve the ability of neurosurgical residents to handle and coordinate endoscopes in performing technically demanding procedures such as neuroendoscopic removal of ventricular tumors or endoscopic third ventriculostomy (ETV).MethodsThe simulator was developed, printed in-house, and evaluated in a trial involving neurosurgery residents who performed ETV and intraventricular tumor resection tasks using it. Participants completed a questionnaire that assessed various aspects of the simulator's effectiveness, including anatomical visualization, procedural understanding, competency enhancement, and subjective impressions.ResultsA total of 12 participants were included in the evaluation. The majority (n = 7, 53.85%) were male, with a mean age of 29.8 ± 3.27 years and 4 ± 2 years of neurosurgical experience. All participants agreed or strongly agreed (4.5 ± 0.50) that the 3D printed simulator helped develop systematic intraventricular visualization and understanding of surgical steps (4.42 ± 0.64). The handling of the endoscope was rated as realistic (4.5 ± 0.50), while the haptic qualities of the tumor were rated lower (3.83 ± 0.80; 3.92 ± 0.64). Training increased competence (4.25 ± 0.45) and coordination skills (4.5 ± 0.50), with 75% (n = 9) feeling more confident with neuroendoscopic instruments and 91.7% (n = 11) in future procedures.ConclusionThe developed 3D-printed simulator offers an accessible and practical training resource for neurosurgical residents, addressing the limitations of traditional training methods. The simulator appears to improve procedural skills and the competence of future neurosurgeons, potentially improving patient safety and outcomes in neurosurgical practice.